Kultur Jaringan Tanaman Anthurium (Anthurium andraeanum var. tropical) pada Media MS dengan Penambahan Zat Pengatur Tumbuh BAP dan NAA - CHOIRI, HERLINDAH; SUADA, I KETUT; ADIARTAYASA, WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.3, Juli 2019, 2019)
Tissue Culture of Anthurium Plants ( Anthurium andraeanum var. tropical) in MS Media with Growth Regulating Substances BAP and NAA   Anthurium ( Anthurium andraeanum var. tropical) is an ornamental plant that has been cultivated on a wide scale in the floriculture industry. The advantages of anthurium ornamental plants has beautiful flowers that are suitable for ornamental plants and cut flowers, and the cut flowers have good opportunities in the domestic and international markets. So makes it suitable to be in-vitro developed to produce seedling that are disease resistant, quality and quantity. This experiment was to determine the optimal concentration of 6-Benzylaminopurine and Napthalene Acetic Acid to induce callus from leaves and shoots from anthurium seeds on Murashige and Skoog base media.  Experiments on leaf explants using factorial completely randomized design with 25 treatment levels of growth regulator substances BAP and NAA. The results showed that BAP and NAA treatments could increase the growth of anthurium plants. The treatment that has the best result in anthurium leaf curvature is A 3 B 2 (5 mg/l NAA + 3 mg/l BAP), with the fastest curvature time is 2 hst and the explant curves 100%. The treatment that has the best results in shoots induction from anthurium seeds is the treatment of A 3 B 3 (5 mg/l NAA + 5 mg/l BAP) with the appearance of shoots at 7.33 days after planting, having 8.92 of shoots, having 3.33 of leaves, and having 5.85 of roots. The A 3 B 3 treatment showed significantly different from the control treatment. The appearance of shoots on control treatment was 8.66 days after planting, having 3.66 of shoots, having 3.33 of leaves,  and having 2.33 of roots. The combination of 5 mg/l BAP + 5 mg/l NAA (A 3 B 3 ) was the best treatment for shoots growth and was suitable for the purpose of multiplying anthurium seedling.